Preparation method of wave-absorbing agent with hollow glass bead-graphene as core-shell structure
By using a hollow glass microsphere-graphene core-shell structure for the preparation of electromagnetic wave absorbers, the impedance mismatch and agglomeration problems of graphene materials in practical applications have been solved, achieving lightweight and efficient electromagnetic wave absorption, which is suitable for weapon stealth and electromagnetic compatibility protection.
Patent Information
- Application Number
- CN202511447832.2
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-10-11
- Publication Date
- 2026-02-03
AI Technical Summary
Existing graphene materials suffer from impedance mismatch, easy agglomeration, and high cost in practical applications, making it difficult to meet the requirements for wide-band electromagnetic wave absorption.
A lightweight and efficient electromagnetic wave absorbing material was prepared by using a hollow glass microsphere-graphene core-shell structure microwave absorbing agent and by precisely controlling the degree of reduction and optimizing the dielectric loss and impedance matching characteristics.
It achieves excellent electromagnetic wave absorption performance over a wide frequency range, and features low density, good corrosion resistance, and low cost, making it suitable for the stealth and electromagnetic compatibility protection of next-generation weapons and equipment.
Smart Images

Figure CN121449342A_ABST
Abstract
Description
TECHNICAL FIELD
[0001] The application relates to the technical field of electromagnetic wave materials, in particular to a preparation method of a wave-absorbing agent with a hollow glass microsphere-graphene core-shell structure. BACKGROUND
[0002] With the continuous development of modern military detection technology, especially radar systems, the survivability of weapon equipment on the battlefield is facing severe challenges. The high-precision reconnaissance and strike integrated system makes it possible to quickly discover and destroy targets, and therefore the stealth performance has become one of the key indicators for evaluating the combat effectiveness of weapons. At the same time, with the wide application of the fifth generation mobile communication technology (5G), the electromagnetic radiation in the environment is increasing, which not only causes interference to precision electronic equipment, but also has the risk of information leakage and position exposure, further promoting the urgent demand for high-performance wave-absorbing materials in the field of national defense and civil protection.
[0003] At present, the design of stealth materials generally pursues the comprehensive performance of being thin, light, wide and strong, that is, thin thickness, low density, wide absorption frequency band and strong absorption capacity. Among many wave-absorbing functional materials, graphene is considered as a potential candidate material due to its high specific surface area, excellent electrical conductivity, high dielectric constant and good chemical stability. However, graphene still has obvious technical bottlenecks in practical application: firstly, due to its high intrinsic conductivity, the impedance is not matched with the free space, and electromagnetic waves are easily reflected on the surface rather than entering the interior to be lost; secondly, the strong π-π interaction between graphene layers easily leads to agglomeration, reducing the effective specific surface area and interface polarization effect; thirdly, the preparation cost is high, which is difficult to meet the demand of large-scale application.
[0004] In order to overcome the above defects, the existing technology has tried to use graphene oxide (GO) and its reduced product (reduced graphene oxide, rGO) as a substitute. By adjusting the reduction degree, the conductivity and dielectric properties can be adjusted to a certain extent, so as to optimize the impedance matching characteristics, enhance the polarization relaxation and conductive loss capacity, and improve the dispersibility and processability. However, at present, the structure-activity relationship between the reduction degree of reduced graphene oxide and its electromagnetic parameters, microstructure and wave-absorbing performance is still lacking in systematic research, especially for the application demand of multi-band and wide-band compatible absorption, the influence mechanism of reduction degree control on its performance still needs to be further clarified.
[0005] Therefore, the application aims to provide a preparation method of a wave-absorbing agent with a hollow glass microsphere-graphene core-shell structure, which optimizes the dielectric loss and impedance matching characteristics in a specific frequency band by accurately controlling the reduction degree, so as to improve the microwave absorption performance of the material in a wide frequency range, and meet the application demand of stealth and electromagnetic compatibility protection of new generation weapon equipment. SUMMARY
[0006] The present application aims to at least solve one of the technical problems existing in the prior art, provide a preparation method of wave absorber with hollow glass microsphere-graphene as core-shell structure.
[0007] To achieve the above-mentioned object, the technical scheme adopted by the present application is as follows: the preparation method of wave absorber with hollow glass microsphere-graphene as core-shell structure comprises the following steps: Step one: disperse the hollow glass microspheres in sodium hydroxide aqueous solution, or treat them in the mixed solution of granular sodium hydroxide and deionized water, react under heating condition, stir for a certain time to introduce hydroxyl functional groups on the surface; after treatment, extract and wash with deionized water until neutral, then dry to obtain hollow glass microspheres containing hydroxyl groups on the surface; Step two: soak the hollow glass microspheres containing hydroxyl groups obtained in step one in silane coupling agent solution and react, stir for a certain time to modify the surface with amino functional groups to facilitate the subsequent compounding with graphene oxide; after the reaction is completed, extract, wash with deionized water, and then dry to obtain modified hollow glass microspheres; Step three: mix the graphene oxide aqueous solution with the modified hollow glass microspheres obtained in step two under heating and stirring conditions, use the amide reaction between the amino groups on the surface of the microspheres and the oxygen-containing functional groups of graphene oxide to realize the coating of graphene oxide on the surface of the microspheres; after the reaction is completed, add the solution to a separatory funnel and stand still, remove the uncoated graphene oxide on the bottom, then wash and extract the product, and dry to obtain a composite material with hollow glass microspheres as the core and graphene oxide coated on the surface; Step four: react the composite material obtained in step three with an appropriate reducing agent under heating condition, stir for a certain time to realize the reduction of graphene oxide; after the reaction is completed, extract and wash, and dry to obtain a wave absorber with hollow glass microsphere-graphene as core-shell structure.
[0008] Further, in step one, the mass ratio of hollow glass microspheres to sodium hydroxide aqueous solution is 1:45-50, the reaction temperature is 80℃, and the reaction time is 2h.
[0009] Further, in step two, the silane coupling agent solution is composed of 3-aminopropyl triethoxysilane, ethanol and water, the addition amount of 3-aminopropyl triethoxysilane is 5wt% of the hollow glass microspheres after surface treatment in step one, the volume ratio of ethanol to water in the mixed solution is 2:1; the reaction temperature is 75℃, and the reaction time is 3h.
[0010] Further, in step three, the graphene oxide aqueous solution is blended from deionized water and graphene oxide solution, the volume ratio of deionized water to graphene oxide solution is 3:2; the reaction temperature is 85℃, and the reaction time is 2h.
[0011] Further, the hollow glass microspheres and graphene oxide in step three have a mass ratio of 5:1.
[0012] Further, the reducing agent in step four is hydrazine hydrate.
[0013] Further, the mass(g)-volume(μL) ratio of the composite material and the reducing agent in step four is 1:160.
[0014] Further, the temperature of the reaction in step four is 85℃, and the reaction time is 5h.
[0015] Further, the mechanical stirrer used in step one, step two and step four has a rotation speed of 200rpm; the mechanical stirrer used in step three has a rotation speed of 100rpm.
[0016] Further, the drying method of step one and step two is vacuum drying box drying, and the drying temperature is 70℃; the drying method of step three and step four is cold dryer drying, and the drying temperature is about-50℃, and the drying time is 20h.
[0017] Compared with the prior art, the technical scheme of the present application has the following beneficial effects: The core-shell structure wave absorber prepared by the present application has the advantages of low density, simple preparation and low cost; the wave absorber realizes lightweight while showing excellent electromagnetic wave absorption performance. In addition, the material also has good corrosion resistance, and especially outstanding is that it can still maintain high electromagnetic wave absorption effect under low density conditions. BRIEF DESCRIPTION OF DRAWINGS
[0018] Figure 1 The SEM image of the core-shell structure wave absorber prepared by example 1 is shown in the figure.
[0019] Figure 2 The SEM image of the core-shell structure wave absorber prepared by example 2 is shown in the figure.
[0020] Figure 3 The SEM image of the core-shell structure wave absorber prepared by example 3 is shown in the figure.
[0021] Figure 4 The SEM image of the core-shell structure wave absorber prepared by example 4 is shown in the figure.
[0022] Figure 5Reflection loss diagram of the core-shell structure wave-absorbing agent with hollow glass microspheres as core and reduced graphene oxide as surface coating prepared in Embodiment 1 of the present application. Wherein, (a) HrG-10; (b) HrG-20; (c) HrG-30; (d) HrG-40.
[0023] Figure 6 Minimum reflection loss and impedance matching diagram of the core-shell structure wave-absorbing agent with hollow glass microspheres as core and reduced graphene oxide as surface coating prepared in Embodiment 1 of the present application.
[0024] Figure 7 Minimum reflection loss and impedance matching diagram of the core-shell structure wave-absorbing agent with hollow glass microspheres as core and reduced graphene oxide as surface coating prepared in Embodiment 2 of the present application.
[0025] Figure 8 Minimum reflection loss and impedance matching diagram of the core-shell structure wave-absorbing agent with hollow glass microspheres as core and reduced graphene oxide as surface coating prepared in Embodiment 3 of the present application. DETAILED DESCRIPTION
[0026] The technical solutions in the present application will be apparently and completely described below with the drawings in the embodiments of the present application. Obviously, the described embodiments are only part of the embodiments of the present application, but not all the embodiments.
[0027] Embodiment 1: A preparation method of a core-shell structure composite wave-absorbing agent (HrG-10) with reduced graphene oxide content of 10%, the preparation steps of which are as follows: Step one: hollow glass microspheres are ultrasonically dispersed in NaOH aqueous solution, and stirring is continuously carried out, then surface treatment is carried out, and after suction filtration, washing is carried out with deionized water and ethanol, and drying is carried out in a vacuum drying box.
[0028] Step two: 3-aminopropyl triethoxysilane (KH550) is taken into a mixed solution of ethanol and water, and the hollow glass microspheres after etching of sodium hydroxide are added into the above mixed solution for reaction. The surface-aminated hollow glass microspheres are prepared, and after suction filtration, washing is carried out with deionized water and ethanol, and drying is carried out in a vacuum drying box.
[0029] Step three: the hollow glass microspheres modified by KH550 are dispersed into deionized water, and then graphene oxide solution is added for stirring. The obtained solution is added into a separatory funnel for standing, and the uncoated graphene oxide on the bottom is removed, so as to prepare the microsphere composite material with hollow glass microspheres as core and graphene oxide as surface coating. After washing with a large amount of deionized water, suction filtration is carried out, and cold drying is carried out in a cold drying machine.
[0030] Step four: take the hollow glass microspheres as the core surface coated with graphene oxide microsphere composite material dispersed in deionized water, using hydrazine hydrate reduction, to obtain the hollow glass microspheres as the core surface coated with reduced graphene oxide core-shell structure composite material, and then dry it by suction filtration and cold drying in a cold drying machine.
[0031] The appearance of the hollow glass microspheres as the core surface coated with reduced graphene oxide core-shell structure wave absorber is black powder, and its morphology presents a spherical structure with a coating on the surface, with a particle size of about 10-20 μm, as shown in Figure 1 .
[0032] The wave absorption performance of the hollow glass microspheres as the core surface coated with reduced graphene oxide core-shell structure wave absorber was tested by a vector network analyzer (VNA). The results showed that the minimum value of the reflection loss was -6.9 dB (f f =12.08 GHz) at a matching thickness of 5.0 mm, and the effective absorption bandwidth (RL<-10 dB) was 0 GHz, as shown in Figure 5 (a).
[0033] The wave absorption performance of the hollow glass microspheres as the core surface coated with reduced graphene oxide core-shell structure wave absorber was tested by a vector network analyzer (VNA). The results showed that the sample impedance matching of HrG-10 was close to 3 at first and then far away from 3, and only a small amount of the sample was close to 1, indicating that its impedance matching performance was poor, and more electromagnetic waves could not enter the material inside for loss, as shown in Figure 6 .
[0034] The mass of the hollow glass microspheres in step one was 10 g, the concentration of the NaOH aqueous solution was 0.5 mol / L, and the solution volume was 400 mL.
[0035] The temperature of the reaction in step one was 80℃, the rotation speed was 200 rpm, and the mechanical stirring time was 2 h, and then it was dried using a vacuum drying box.
[0036] The mass of 3-aminopropyl triethoxysilane (KH550) in step two was 0.5 g, the volume ratio of ethanol to water in the mixed solution was 2:1, and the total solution volume was 225 mL.
[0037] The temperature of the reaction in step two was 75℃, the rotation speed was 200 rpm, and the mechanical stirring time was 3 h, and then it was dried using a vacuum drying box.
[0038] The mass of the KH550 modified hollow glass microspheres in step three was 2 g, the deionized water solution volume was 80 mL, and the graphene oxide solution concentration was 0.01 g / mL, and the solution volume was 20 mL.
[0039] The temperature of the reaction in step three is 85℃, the rotation speed is 100rpm, the mechanical stirring time is 2h, and the drying time in the cold dryer is 20h.
[0040] The mass of the microsphere composite material with hollow glass microspheres as the core and graphene oxide coated on the surface in step four is 1g, the volume of the deionized water solution is 100mL, and the volume of the hydrazine hydrate solution is 160μL.
[0041] The temperature of the reaction in step four is 85℃, the rotation speed is 200rpm, the mechanical stirring time is 5h, and the drying time in the cold dryer is 20h.
[0042] Example 2: A method for preparing a core-shell structure composite wave-absorbing agent (HrG-20) with a reduced graphene oxide content of 20% includes the following steps: Step one: Hollow glass microspheres are ultrasonically dispersed in a NaOH aqueous solution, and stirring is continuously performed, followed by surface treatment, suction filtration, washing with deionized water and ethanol, and drying in a vacuum drying oven.
[0043] Step two: 3-aminopropyltriethoxysilane (KH550) is placed in a mixed solution of ethanol and water, and the hollow glass microspheres etched after the addition of sodium hydroxide are added to the mixed solution for reaction. Aminated hollow glass microspheres are prepared, followed by suction filtration, washing with deionized water and ethanol, and drying in a vacuum drying oven.
[0044] Step three: The hollow glass microspheres modified by KH550 are dispersed in deionized water, and graphene oxide solution is added for stirring. The obtained solution is added to a separatory funnel for standing, and uncoated graphene oxide settled at the bottom is removed, so as to prepare microsphere composite materials with hollow glass microspheres as the core and graphene oxide coated on the surface. After washing with a large amount of deionized water, suction filtration, and drying in a cold dryer.
[0045] Step four: The microsphere composite materials with hollow glass microspheres as the core and graphene oxide coated on the surface are dispersed in deionized water, and hydrazine hydrate is used for reduction, so as to prepare a core-shell structure composite material with hollow glass microspheres as the core and reduced graphene oxide coated on the surface. After suction filtration and drying, the material is dried in a cold dryer.
[0046] The core-shell structure wave-absorbing agent with hollow glass microspheres as the core and reduced graphene oxide coated on the surface has a dark green powder appearance, and the SEM test shows that the morphology presents a spherical structure with a coating on the surface, and the particle size is about 10-20μm, as shown in Figure 4 .
[0047] The hollow glass microspheres coated with reduced graphene oxide were tested by a vector network analyzer (VNA) for wave-absorbing performance. The results show that the minimum value of the reflection loss is -20.54 dB (f=8.16 GHz) at a matching thickness of 5 mm, and the effective absorption bandwidth (RL<-10 dB) is 4.4 GHz, as shown in f (b). Figure 5
[0048] The hollow glass microspheres coated with reduced graphene oxide were tested by a vector network analyzer (VNA) for wave-absorbing performance. The results show that the sample impedance matching of HrG-20 is close to 1 at first and then far from 1, and the sample has more regions close to 1, indicating that the impedance matching performance is good, so that more electromagnetic waves can enter the material inside for loss, as shown in Figure 7 .
[0049] The mass of the hollow glass microspheres in step one is 10 g, the concentration of the NaOH aqueous solution is 0.5 mol / L, and the solution volume is 400 mL.
[0050] The temperature of the reaction in step one is 80℃, the rotation speed is 200 rpm, the mechanical stirring time is 2 h, and a vacuum drying box is used for drying.
[0051] The mass of 3-aminopropyl triethoxysilane (KH550) in step two is 0.5 g, the volume ratio of ethanol to water in the mixed solution is 2:1, and the total solution volume is 225 mL.
[0052] The temperature of the reaction in step two is 75℃, the rotation speed is 200 rpm, the mechanical stirring time is 3 h, and a vacuum drying box is used for drying.
[0053] The mass of the hollow glass microspheres modified by KH550 in step three is 2 g, the deionized water solution volume is 60 mL, the concentration of the graphene oxide solution is 0.01 g / mL, and the solution volume is 40 mL.
[0054] The temperature of the reaction in step three is 85℃, the rotation speed is 100 rpm, the mechanical stirring time is 2 h, and a cold dryer is used for drying for 20 h.
[0055] The mass of the microsphere composite material coated with graphene oxide on the surface of the hollow glass microbeads in step four is 1 g, the deionized water solution volume is 100 mL, and the hydrazine hydrate solution volume is 160 μL.
[0056] The temperature of the reaction in step four is 85℃, the rotation speed is 200 rpm, the mechanical stirring time is 5 h, and a cold dryer is used for cold drying for 20 h.
[0057] Example 3: A method for preparing a core-shell structured composite microwave absorber (HrG-30) with a reduced graphene oxide content of 30% includes the following steps: Step 1: Take hollow glass microspheres and ultrasonically disperse them in NaOH aqueous solution while continuously stirring. Then, perform surface treatment, filter, wash with deionized water and ethanol, and dry in a vacuum drying oven.
[0058] Step 2: 3-Aminopropyltriethoxysilane (KH550) was placed in a mixed solution of ethanol and water. Hollow glass microspheres etched with sodium hydroxide were then added to the mixed solution to initiate the reaction. Amination-coated hollow glass microspheres were obtained, filtered, washed with deionized water and ethanol, and dried in a vacuum drying oven.
[0059] Step 3: Disperse the KH550 modified hollow glass microspheres in deionized water, then add graphene oxide solution and stir. Add the resulting solution to a separatory funnel and let it stand to remove any uncoated graphene oxide that settles to the bottom. This produces a microsphere composite material with hollow glass microspheres as the core and graphene oxide coating on the surface. After washing with a large amount of deionized water, filter and then air-dry in a refrigerated dryer.
[0060] Step 4: Disperse the microsphere composite material with hollow glass microspheres as the core and graphene oxide coating on the surface in deionized water, reduce it with hydrazine hydrate to prepare a core-shell structure composite material with hollow glass microspheres as the core and reduced graphene oxide coating on the surface. After filtration and drying, it is then cold-dried in a refrigerated dryer.
[0061] The core-shell structured microwave absorber, with hollow glass microspheres as the core and reduced graphene oxide coated on the surface, appears as a dark green powder. SEM analysis revealed a spherical structure with a surface coating, and the particle size was approximately 10-20 μm. Figure 3 As shown.
[0062] The microwave absorption performance of a core-shell structured absorber with hollow glass microspheres coated with reduced graphene oxide was tested using a vector network analyzer (VNA). The results showed that the minimum reflection loss was -30.68 dB when the matching thickness was 5 mm. f =8.08GHz), with an effective absorption bandwidth (RL<-10dB) of 5.01GHz, such as Figure 5 As shown in (c).
[0063] The microwave absorption performance of a core-shell structured microwave absorber with hollow glass microspheres coated with reduced graphene oxide was tested using a vector network analyzer (VNA). The results showed that the impedance matching of the HrG-30 sample initially approached and then moved away from 1, with more regions of the sample approaching 1, indicating good impedance matching performance. This allows more electromagnetic waves to penetrate the material for dissipation. Figure 8 As shown.
[0064] The mass of the hollow glass microspheres in step one is 10 g, the concentration of the NaOH aqueous solution is 0.5 mol / L, and the volume of the solution is 400 mL.
[0065] The temperature of the reaction in step one is 80℃, the rotation speed is 200 rpm, the mechanical stirring time is 2 h, and a vacuum drying box is used for drying.
[0066] The mass of the 3-aminopropyl triethoxysilane (KH550) in step two is 0.5 g, the volume ratio of ethanol to water in the mixed solution is 2:1, and the total volume of the solution is 225 mL.
[0067] The temperature of the reaction in step two is 75℃, the rotation speed is 200 rpm, the mechanical stirring time is 3 h, and a vacuum drying box is used for drying.
[0068] The mass of the hollow glass microspheres modified by KH550 in step three is 2 g, the volume of the deionized water solution is 40 mL, the concentration of the graphene oxide solution is 0.01 g / mL, and the volume of the solution is 60 mL.
[0069] The temperature of the reaction in step three is 85℃, the rotation speed is 100 rpm, the mechanical stirring time is 2 h, and a cold drying machine is used for drying for 20 h.
[0070] The mass of the microsphere composite material with hollow glass beads as the core and graphene oxide coated on the surface in step four is 1 g, the volume of the deionized water solution is 100 mL, and the volume of the hydrazine hydrate solution is 160 μL.
[0071] The temperature of the reaction in step four is 85℃, the rotation speed is 200 rpm, the mechanical stirring time is 5 h, and a cold drying machine is used for cold drying for 20 h.
[0072] Example 4: A preparation method of a core-shell structure composite wave-absorbing agent (HrG-40) with a reduced graphene oxide content of 40%, the preparation steps of which are as follows: Step one: Hollow glass microspheres are ultrasonically dispersed in an NaOH aqueous solution, and constant stirring is performed, followed by surface treatment, washing with deionized water and ethanol, and drying in a vacuum drying box.
[0073] Step two: 3-aminopropyl triethoxysilane (KH550) is placed in a mixed solution of ethanol and water, and the hollow glass microspheres etched by sodium hydroxide are added to the mixed solution for reaction. The surface-aminated hollow glass microspheres are obtained, washed with deionized water and ethanol, and dried in a vacuum drying box.
[0074] Step three: take the hollow glass microspheres modified by KH550 and disperse them in deionized water, then add graphene oxide solution and stir. Then add the obtained solution to a separatory funnel and stand, remove the uncoated graphene oxide that has settled to the bottom, to obtain a microsphere composite material with hollow glass microspheres as the core and graphene oxide coated on the surface. Wash with a large amount of deionized water, then filter and dry in a cold dryer.
[0075] Step four: take the microsphere composite material with hollow glass microspheres as the core and graphene oxide coated on the surface, disperse it in deionized water, and reduce it using hydrazine hydrate to obtain a core-shell structure composite material with hollow glass microspheres as the core and reduced graphene oxide coated on the surface. After drying by filtration, dry in a cold dryer.
[0076] The core-shell structure wave absorber with hollow glass microspheres as the core and reduced graphene oxide coated on the surface has a dark green powder appearance. The SEM test shows that the morphology presents a spherical structure with a coating on the surface, and the particle size is about 10-20 μm, as shown in Figure 4 .
[0077] The core-shell structure wave absorber with hollow glass microspheres as the core and reduced graphene oxide coated on the surface was tested for wave absorption performance by a vector network analyzer (VNA). The results show that the minimum value of the reflection loss of HrG-40 sample is -11.92 dB (f f = 10.64 GHz) at a matching thickness of 3.0 mm, and the effective absorption bandwidth (RL <-10 dB) is 6.46 GHz, as shown in Figure 5 (d).
[0078] In step one, the mass of the hollow glass microspheres is 10 g, the concentration of the NaOH aqueous solution is 0.5 mol / L, and the volume of the solution is 400 mL.
[0079] In step one, the reaction temperature is 80°C, the rotation speed is 200 rpm, and the mechanical stirring time is 2 h, and a vacuum drying oven is used for drying.
[0080] In step two, the mass of 3-aminopropyl triethoxysilane (KH550) is 0.5 g, the volume ratio of ethanol to water in the mixed solution is 2:1, and the total volume of the solution is 225 mL.
[0081] In step two, the reaction temperature is 75°C, the rotation speed is 200 rpm, and the mechanical stirring time is 3 h, and a vacuum drying oven is used for drying.
[0082] In step three, the mass of the hollow glass microspheres modified by KH550 is 2 g, the volume of the deionized water solution is 20 mL, and the concentration of the graphene oxide solution is 0.01 g / mL, and the volume of the solution is 80 mL.
[0083] The temperature of the reaction in step three is 85℃, the rotating speed is 100rpm, the time of mechanical stirring is 2h, and the drying time is 20h.
[0084] The mass of the microsphere composite material with hollow glass microspheres as the core and graphene oxide coated on the surface in step four is 1g, the volume of the deionized water solution is 100mL, and the volume of the hydrazine hydrate solution is 160μL.
[0085] The temperature of the reaction in step four is 85℃, the rotating speed is 200rpm, the time of mechanical stirring is 5h, and the drying time is 20h.
[0086] In the absence of conflicts, the above additional technical features can be combined and used by those skilled in the art.
[0087] It can be understood that the present application is described by some embodiments, and those skilled in the art know that various changes or equivalent replacements can be made to the features and embodiments without departing from the spirit and scope of the present application. In addition, under the guidance of the present application, the features and embodiments can be modified to adapt to specific conditions and materials without departing from the spirit and scope of the present application. Therefore, the present application is not limited by the specific embodiments disclosed herein, and all embodiments falling within the scope of the claims of the present application are within the scope of the present application.
Claims
1. A method for preparing a microwave absorbing agent with a core-shell structure of hollow glass microspheres-graphene, characterized in that, Includes the following steps: Step 1: Disperse hollow glass microspheres in an aqueous sodium hydroxide solution, or treat them in a mixed solution of granular sodium hydroxide and deionized water, react under heating conditions, and stir for a certain time to introduce hydroxyl functional groups on the surface; after treatment, filter, wash with deionized water until neutral, and then dry to obtain hollow glass microspheres with hydroxyl groups on the surface. Step 2: The hollow glass microspheres with hydroxyl groups on the surface obtained in Step 1 are immersed in a silane coupling agent solution and stirred for a certain period of time to modify the surface with amino functional groups to promote subsequent composite with graphene oxide; after the reaction is completed, the microspheres are filtered, washed with deionized water, and then dried to obtain modified hollow glass microspheres. Step 3: The aqueous solution of graphene oxide is mixed with the modified hollow glass microspheres obtained in Step 2 under heating and stirring conditions. The amino groups on the surface of the microspheres undergo an amidation reaction with the oxygen-containing functional groups of graphene oxide to achieve the coating of graphene oxide on the surface of the microspheres. After the reaction is completed, the solution is added to a separatory funnel and allowed to stand. After removing the uncoated graphene oxide that settles to the bottom, the product is washed, filtered, and dried to obtain a composite material with hollow glass microspheres as the core and graphene oxide coating on the surface. Step 4: The composite material obtained in Step 3 is reacted with an appropriate amount of reducing agent under heating conditions and stirred for a certain time to achieve the reduction of graphene oxide; after the reaction is completed, it is filtered, washed, and dried to obtain a microwave absorbing agent with hollow glass microspheres-graphene as the core-shell structure.
2. The method for preparing a microwave absorbing agent with a core-shell structure of hollow glass microspheres-graphene according to claim 1, characterized in that: In step one, the mass ratio of hollow glass microspheres to sodium hydroxide aqueous solution is 1:45-50, the reaction temperature is 80℃, and the reaction time is 2h.
3. The method for preparing a microwave absorbing agent with a core-shell structure of hollow glass microspheres-graphene according to claim 1, characterized in that: In step two, the silane coupling agent solution is composed of 3-aminopropyltriethoxysilane, ethanol, and water. The amount of 3-aminopropyltriethoxysilane added is 5 wt% of the surface-treated hollow glass microspheres taken in step one, and the volume ratio of ethanol to water in the mixed solution is 2:
1. The reaction temperature is 75℃ and the reaction time is 3h.
4. The method for preparing a microwave absorbing agent with a core-shell structure of hollow glass microspheres-graphene according to claim 1, characterized in that: In step three, the graphene oxide aqueous solution is prepared by mixing deionized water and graphene oxide solution, with a volume ratio of 3:2; the reaction temperature is 85℃ and the reaction time is 2h.
5. The method for preparing a microwave absorbing agent with a core-shell structure of hollow glass microspheres-graphene according to claim 1, characterized in that: In step three, the mass ratio of hollow glass microspheres to graphene oxide is 5:
1.
6. The method for preparing a microwave absorbing agent with a core-shell structure of hollow glass microspheres-graphene according to claim 1, characterized in that: The reducing agent in step four is hydrazine hydrate.
7. The method for preparing a microwave absorbing agent with a core-shell structure of hollow glass microspheres-graphene according to claim 1, characterized in that: In step four, the mass (g)-volume (μL) ratio of the composite material to the reducing agent is 1:
160.
8. The method for preparing a microwave absorbing agent with a core-shell structure of hollow glass microspheres-graphene according to claim 1, characterized in that: The reaction temperature in step four is 85°C, and the reaction time is 5 hours.
9. The method for preparing a microwave absorbing agent with a core-shell structure of hollow glass microspheres-graphene according to claim 1, characterized in that: Steps one, two, and four use a mechanical stirrer with a rotation speed of 200 rpm; step three uses a mechanical stirrer with a rotation speed of 100 rpm.
10. The method for preparing a microwave absorbing agent with a core-shell structure of hollow glass microspheres-graphene according to claim 1, characterized in that: The drying methods for steps one and two are both vacuum drying oven drying at a temperature of 70°C; the drying methods for steps three and four are refrigerated dryer drying at a temperature of approximately -50°C for 20 hours.